Oxidative stress-driven enhanced iron production and scavenging through Ferroportin reorientation worsens anemia in antimony-resistant Leishmania donovani infection. - Souradeepa Ghosh; Krishna Vamshi Chigicherla; Shirin Dasgupta; Yasuyuki Goto; Budhaditya Mukherjee (PLoS Pathogens)
Despite the withdrawal of pentavalent-antimonials in treating Visceral leishmaniasis from India, recent clinical isolates of Leishmania donovani (LD) exhibit unresponsiveness towards pentavalent-antimony (LD-R). This antimony-unresponsiveness points towards a genetic adaptation that underpins LD-R's evolutionary persistence and dominance over sensitive counterparts (LD-S). This study highlights how LD evolutionarily tackled antimony exposure and gained increased potential of scavenging host-iron within its parasitophorous vacuoles (PV) to support its aggressive proliferation. Even though anti-leishmanial activity of pentavalent antimonials relies on triggering oxidative outburst, LD-R exhibits a surprising strategy of promoting reactive oxygen species (ROS) generation in infected macrophages. An inherent metabolic shift from glycolysis to Pentose Phosphate shunt allows LD-R to withstand elevated ROS by sustaining heightened levels of NADPH. Elevated ROS levels on the other hand trigger excess iron production, and LD-R capitalizes on this surplus iron by selectively reshuffling macrophage-surface iron exporter, Ferroportin, around its PV thereby gaining a survival edge as a heme-auxotroph. Higher iron utilization by LD-R leads to subsequent iron insufficiency, compensated by increased erythrophagocytosis through the breakdown of SIRPα-CD47 surveillance, orchestrated by a complex interplay of two proteases, Furin and ADAM10. Understanding these mechanisms is crucial for managing LD-R-infections and their associated complications like severe anemia, and may also provide valuable mechanistic insights into understanding drug unresponsiveness developed in other intracellular pathogens that rely on host iron.